1996
DOI: 10.1074/jbc.271.2.726
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of an Endogenous Peptide from Rat Brain Interacting Specifically with the Serotonergic 1B Receptor Subtypes

Abstract: The existence of endogenous compounds interacting with the serotonergic system was previously postulated. In the present work, rat brain tissues were extracted by acidic and organic procedures. The resulting extract was tested for its capacity to interact with the binding of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Data replotted from Lane et al (2014). well-validated allosteric modulators of signaling via the CaSR (Conigrave et al, 2000;Busque et al, 2005;Conigrave and Hampson, 2010;Liou et al, 2011), and a role for L-Leu as an endogenous modulator of the GABA B receptor has also been proposed (Kerr and Ong, 2003). Another endogenous allosteric modulator of the CaSR is the g-glutamyl-peptide glutathione (Broadhead et al, 2011), whereas the tetrapeptide "5HT-moduline" (Leu-Ser-Ala-Leu) has been proposed as an endogenous modulator of the 5HT 1B receptor in the central nervous system Massot et al, 1996;Rousselle et al, 1996). More recently, studies in mouse and hamster brain tissues identified a family of peptides, known as the pepcans, that have been proposed as endogenous allosteric modulators of the cannabinoid CB 1 receptor (Bauer et al, 2012).…”
Section: Endogenous Allosteric Modulatorsmentioning
confidence: 99%
“…Data replotted from Lane et al (2014). well-validated allosteric modulators of signaling via the CaSR (Conigrave et al, 2000;Busque et al, 2005;Conigrave and Hampson, 2010;Liou et al, 2011), and a role for L-Leu as an endogenous modulator of the GABA B receptor has also been proposed (Kerr and Ong, 2003). Another endogenous allosteric modulator of the CaSR is the g-glutamyl-peptide glutathione (Broadhead et al, 2011), whereas the tetrapeptide "5HT-moduline" (Leu-Ser-Ala-Leu) has been proposed as an endogenous modulator of the 5HT 1B receptor in the central nervous system Massot et al, 1996;Rousselle et al, 1996). More recently, studies in mouse and hamster brain tissues identified a family of peptides, known as the pepcans, that have been proposed as endogenous allosteric modulators of the cannabinoid CB 1 receptor (Bauer et al, 2012).…”
Section: Endogenous Allosteric Modulatorsmentioning
confidence: 99%
“…Likewise, the calcium receptor is activated allosterically (enhanced sensitivity to Ca 2ϩ ) by several classes of Lamino acids including L-phenylalanine and L-tryptophan (Lee et al, 2007). Another natural allosteric modulator initially purifed from rat brain is the tetrapeptide Leu-Ser-Ala-Leu (LSAL; later named 5-HT moduline), which selectively reduces the binding of 5-HT to the 5-HT 1B receptor Rousselle et al, 1996).…”
Section: A Classic Guest Allosterismmentioning
confidence: 99%
“…We have previously shown that both auto-and hetero-presynaptic r5-HT 1B receptors were desensitized immediately under stress conditions (15). Moreover, an increase in synthesis, release, and turnover of 5-HT has been observed in the brain of animals subjected to stress (16-19).5-HT-moduline is a cerebral tetrapeptide that was recently isolated and characterized in our laboratory (20,21). We have shown by in vivo and in vitro studies that functional activities of 5-HT 1B receptor subtypes were significantly decreased by this tetrapeptide.…”
mentioning
confidence: 99%
“…We have shown by in vivo and in vitro studies that functional activities of 5-HT 1B receptor subtypes were significantly decreased by this tetrapeptide. 5-HT-moduline may interact with r5-HT 1B and h5-HT 1B receptors at the molecular level by noncompetitive mechanisms and at the functional level by interacting with 5-HT release (20,21). This tetrapeptide may therefore play a fundamental role in various pathological conditions such as depression and anxiety.…”
mentioning
confidence: 99%